ANALISA GANGGUAN HUBUNG SINGKAT DENGAN MENGGUNAKAN ETAP 12.6.0 PADA PT X - Badaruddin Badaruddin (Universitas Muhammadiyah Tangerang, 2016)
ConstructionofcoalhandlingfacilityPTXdemandingtheneedforan analysisofthe equipmentratingcircuitbreaker(CircuitBreaker),sothatthe CircuitBreaker(CB)can secure thepowersystemagainstharmfulinterference,especiallyinterference symmetrical short-circuitthree-phase.Foritwas doneastudyofshortcircuitintheelectricpower system.Calculationofthesymmetricalshort-circuitfaultcurrentis basedonsoftware simulationETAP 12.6. The conclusionisthatthe biggestfaultcurrent. The results obtainedforsymmetricalthree-phasedisorders,thegreatestdisruptionoccursinLV MCCbus(400V) withinitialsymmetricalfaultcurrent(I